2020
DOI: 10.1002/bdr2.1645
|View full text |Cite
|
Sign up to set email alerts
|

5‐year experience of a tertiary center in major congenital abnormalities in singleton pregnancies

Abstract: Objective: To demonstrate major congenital abnormalities delivered or terminated at our institution between 2014 and 2018.Materials and Methods: Necessary information was retrieved from the registries of the delivery room and electronic database of Hacettepe University Hospital, Ankara. Results: This study was consisted of 307 major congenital anomalies. The incidence of major congenital anomalies was 2.9 per 1,000 live births, while the majority of the cases were related to cardiovascular, central nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In this study, the central nervous system was the most common type of structural anomalies among both singleton and twin pregnancies. In a previous study, the most common fetal malformations were cardiovascular system malformations, central nervous system malformations and diaphragmatic hernias in singletons 16 . Another study found that the main cause of termination of pregnancy in twin pregnancies was fetal central nervous system malformation 6 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, the central nervous system was the most common type of structural anomalies among both singleton and twin pregnancies. In a previous study, the most common fetal malformations were cardiovascular system malformations, central nervous system malformations and diaphragmatic hernias in singletons 16 . Another study found that the main cause of termination of pregnancy in twin pregnancies was fetal central nervous system malformation 6 .…”
Section: Discussionmentioning
confidence: 92%
“…In a previous study, the most common fetal malformations were cardiovascular system malformations, central nervous system malformations and diaphragmatic hernias in singletons. 16 Another study found that the main cause of termination of pregnancy in twin pregnancies was fetal central nervous system malformation. 6 Glinianaia et al 7 also found that twins had higher rates of all major types of congenital anomalies than singletons, including central nervous/musculoskeletal/genitourinary system malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of congenital abnormalities is also important for offering parents all choices, including TOP, both for ethical and legal reasons ( 8 , 9 ). Therefore, TOP is a critical decision that should be taken through a multidisciplinary committee with the parents involvement ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fetal anomalies diagnosed in advanced weeks due to delaying of prenatal diagnosis at earlier gestational weeks may survive despite their anomalies due to improvements in newborn care support units and facilities. However, severe anomalies mostly lead to recurrent interventions and increased morbidity and mortality ( 10 , 20 ).…”
Section: Discussionmentioning
confidence: 99%